Power Relations between Parents and Children in The Novel My Life As A Stuntboy - Agna Sita Novela (Passage, 2017)
The novel entitled My Life as a Stuntboy is one of adolescent novels that has several issues to explore. The issue of power relation becomes the main focus of the present research, which is aimed to answer the question of what meanings can be made from the portrayal of parent–child power relation. Power relation in the novel is seen through the conflicts that occur specifically between parents and their child as the main characters of this novel. The data were analyzed by using Dekovic, Gracia-Ruiz, Hernandez-Cabrera, Maiquez, and Rodrigo (2012) conflict resolutions: negotiation and dominance, and Foucault’s (2003/2006) theory of power that states the power which occurs in familial relations includes sovereignty and disciplinary power. The findings of the research revealed that the conflicts in the parent-child relationship are triggered by parents’ expectations toward their child. The conflicts involved the issues related to studying, Frank the monkey, and the child’s wish. Overall, these conflicts were caused by the parents’ demands for the child to be more responsible. The role of society is also found to have affected the parents’ expectations toward their child’s behavior and future. Therefore, based on the findings, it can be concluded that the meaning that can be made from the portrayal of parent–child relationship is that parents use their power to teach their child to be responsible citizen.Keywords: adolescent literature, conflicts, power relations, parent-child relation